Os entes Federais na pandemia e o papel do STF - ABREU, Wanderson Carlos Medeiros (2023)
This research aims to demonstrate the relationship between the COVID-19 pandemic and a possible weakening of the Brazilian federal model. Based on a jurisprudential analysis of actions between 2020 and 2022 by the Federal Supreme Court (STF), it is inferred how the behavior of federative entities may have triggered or evidenced a crisis in the federative pact in Brazil. Initially, it addressed how the federal system was redesigned to align with the Federal Constitution of 1988 and, in accordance with a comparative analysis, how other modern democracies dialogue with the federal system of their countries. Next, it was necessary to understand how federalism manifested itself in Brazil, in accordance with constitutional provisions, in order to describe a portrait of health based on a path of cooperation between the federal spheres. Finally, the problematization promised by the research was reached, addressing federal conflicts in Brazil and how federal entities behaved during the pandemic, in addition to addressing whether the STF has privileged the Union or subnational entities in this divergence. For this, it was essential to understand the role of the Federal Supreme Court in the face of federal conflicts and the need (or not) for its intervention. Thus, using the inductive and legal-descriptive methods and complementing it with jurisprudential analysis, this research analyzed several actions in the STF's constitutionality control in order to confirm the hypothesis about the relationship between the pandemic and the possible rupture of the federative pact of Brazil.